Hemodynamic and antiarrhythmic effects of lidocaine or amiodarone in dogs anesthetized with halothane - Moro, J.v. [UNESP]; Nunes, N. [UNESP]; Barbosa, V.f. [UNESP]; Thiesen, R. [UNESP]; Lopes, P.c.f. [UNESP]; Belmonte, E.a. [UNESP]; Borges, P.a. [UNESP]; Batista, P.a.c.s. [UNESP]; Costa, P.f. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The effects of continuous rate infusion of lidocaine or amiodarone on hemodynamic and arrhythmias induced by epinephrine in dogs anesthetized with halothane were evaluated. Thirty dogs were distributed into three groups: amiodarone group (AG), lidocaine group (LG), or control group (CG). Anesthesia was induced with etomidate and maintained with halothane. Thirty minutes later a bolus and continuous rate infusion (CRI) of amiodarone in AG, lidocaine in LG and NaCl at 0.9% in CG was administered. After 10 minutes, arrhythmias were induced by epinephrine CRI at 0.0001mg/kg/minute, which was increased in 0.0001mg/kg/minute every ten minutes, until 0.0003mg/kg/minute. The measurements were performed 30 minutes after the induction of anesthesia (T0), 10 minutes after beginning the drug CRIs (T1), 10 minutes after beginning epinephrine administration (T2) and 10 minutes after increasing epinephrine CRI (T3 and T4). In CG, at T3 heart rate (HR) was greater than in LG, while at T4, HR in GC was higher than in LG and AG. In LG and CG, from T2, central venous pressure (CVP), cardiac index (CI), systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), mean pulmonary arterial pressure (mPAP) increased. In AG, SAP, DAP and MAP it decreased from T1 to T3. The ventricular ectopic beats (VEB) were lower in AG. Amiodarone has better antiarrhythmogenic effects, although it was also associated with hypotension.

Avaliaram-se os efeitos da infusão contínua de lidocaína ou amiodarona sobre a hemodinâmica e as arritmias induzidas pela epinefrina em cães anestesiados com halotano. Trinta animais foram distribuídos em três grupos: grupo amiodarona (GA), grupo lidocaína (GL) ou grupo-controle (GC). A anestesia foi induzida com etomidato e mantida com halotano. Trinta minutos após, foram administrados bolus e infusão contínua (CRI) de amiodarona no GA, de lidocaína no GL e de NaCl a 0,9% no GC. Após 10 minutos, iniciou-se a CRI de epinefrina (0,0001mg/kg/minuto), aumentando-se 0,0001mg/kg/minuto a cada 10 minutos até 0,0003mg/kg/minuto. As mensurações foram realizadas 30 minutos após a indução anestésica (T0), 10 minutos após a CRI dos fármacos (T1), 10 minutos após a administração de epinefrina (T2) e a cada 10 minutos após o incremento na CRI de epinefrina (T3 e T4). A frequência cardíaca (FC) foi maior no GC que no GL em T3 e maior em GC que nos demais grupos em T4. A partir de T2, houve aumento na pressão venosa central (PVC), no índice cardíaco (IC), nas pressões arteriais sistólica (PAS), diastólica (PAD) e média (PAM) e na pressão média da artéria pulmonar (PAPm) no GL e no GC. No GA, PAS, PAD e PAM diminuíram de T1 a T3. Os batimentos ventriculares ectópicos (BVE) foram menores no GA. Amiodarona possui melhores efeitos antiarrítmicos, apesar de também estar associada com hipotensão.
Efeitos hemodinâmicos e antiarrítmicos da lidocaína ou amiodarona em cães anestesiados com halotano
Keywords: cães; antiarritmogenicidade; anestesia; canine; antiarrhythmogenicity; anesthesia